Identification of a Potential RNAzyme in Brucella abortus with Heme-Dependent Peroxidase Activity - Chapman, Dalton L (East Carolina University, 2020)
Bovine brucellosis is of significant concern to the U.S. cattle industry and has not been controlled by vaccination in some areas of the world. The inability to control this pathogen is currently a serious public health concern because infected animals or animal products can readily transmit brucellosis to humans with an extremely low infectious dose of 10-100 organisms (Neta et al., 2010, Franz, D.R. 1997). The characteristics of Brucella such as the extreme variability of symptoms it causes, as well as its durability and small size, deem it an attractive bioweapon and highlight the necessity for understanding its virulence mechanisms. Iron (Fe) is an essential micronutrient for almost all microorganisms for a variety of cellular processes. Interestingly, heme is a biologically relevant source of iron for Brucella during infection (Roop, 2011), and the operon bhuTUV works in conjunction with the outer membrane heme transporter BhuA to bring heme into B. abortus (Ojeda, 2012). Interesting, a putative open reading frame (ORF) with an unknown function lies upstream of bhuTUV. Catalase activity is also important to Brucella, and the sole catalase produced by B. abortus 2308 plays a minimal role in detoxifying endogenous H2O2 (Steele et al., 2010). Interestingly, there is strong evidence that DNA and RNA can fold to create cofactor-binding sites capable of binding heme at the submicromolar level by folding into a guanine-quadruplex (Kong et al., 2010, Travascio et al., 1998, Travascio et al., 1999, Poon et al., 2011). Characteristics of oligonucleotides folding into G-quadruplexes also who peroxidase activity. However, this activity has only been shown in vitro and not in any living organism. This study aimed to determine if the hypothetical ORF upstream of the bhuTUV operon (named KAPF) possesses heme-dependent peroxidase activity by also folding into a guanine-quadruplex. Qualitative and quantitative in vitro and in vivo analyses were performed in this study to determine if KAPF acts in this way to rid of endogenous H2O2 in the cell. Furthermore, this work contributed to filling in the knowledge gap regarding the various ways Brucella responds to heme. RNAseq data suggested that an RNA product of KAPF was produced, regardless of iron concentration. It was predicted that this segment is not only a transcriptional start site but is also turned on continuously to act as an RNAzyme with peroxidase activity by folding into a G-quadruplex and interacting with heme. This study found that KAPF binds heme in vitro and significantly more than nucleotides previously known to bind heme. However, no peroxidase activity was detected in vitro or in vivo. This led to an alternative hypothesis as to why the bhuTUV operon is not transcribed when an RNA product of KAPF is produced. A riboswitch may be causing the termination of downstream genes in response to heme. This introduces a never-before described heme riboswitch and potentially fills the knowledge gap surrounding this segment of interest's response to heme. It is imperative to fill any knowledge gaps associated with Brucella virulence mechanisms in order to relieve any concerns regarding the impact brucellosis has on the overall health of agriculture and humans.
Keywords: RNAzyme; riboswitch; Brucella abortus; Heme